Central Government Authority in Environmental Management in Provinces - Luh Ketut Ayu Manik Sastrini (Universitas Bali Dwipa, 2021)
The authority of the Central Government and Regional Governments in environmental management is very large, so there needs to be clear restrictions on environmental management. With the authority possessed by the Regional Government, it is necessary to have a good form of supervision carried out by the Central Government so that various policies that damage the environment do not occur in the province. The Central Government must be active in conducting supervision so that environmentally sound development can be carried out properly by the Central Government and Regional Governments. If there are various problems that arise, the central government must handle them properly because the central government still has the authority to conduct various policy evaluations carried out by local governments so that local governments can exercise their authority proportionally in the field of environmental management. The Regional Government has the authority to manage the environment in the province. In carrying out government affairs under its authority, the regional government has the right to make policies in order to increase community participation in regional development. Law No. 9 of 2015 in conjunction with Law No. 23 of 2014 concerning Regional Government, there is a division of government affairs between the central government and local governments. The authority of the regional government is the authority that comes from the delegation of authority by the government to the autonomous region. The authority delegated to local governments, especially in environmental management, must be clearly regulated in a statutory regulation. Sustainable environmental management is a continuous environmental management. In this way, the impact of environmental management that is implemented will be felt in the long term. So that it can be felt by our next generation continuously.